Islam And Mosque Management in Ghana: Challenges and Prospects - Mustapha Abdullah Kuyateh (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2020)
In the early days of Islam, a mosque was more than just a place of spiritual solace. It also served as an educational and community service Centre. Community affairs were deliberated upon in the sublime tranquility of the mosque. This is in line with the mosque being a multi-functional institution and its centrality as a prime agency to facilitate the creation of an excellent mosque community. In most Muslim communities in Ghana, it is not clear who are tasked with the responsibility of managing and maintaining the mosque. In some communities, it is the Imam. In others, it is manned by volunteers. In most urban communities in Ghana, it is the Mosque Management Committee which is tasked to manage the affairs of the mosque. Within this committee, there is no stipulated qualification for membership. This makes it difficult, if not impossible for them to deliver to expectation. The interesting thing is that this committee is not accountable to the congregation since there is lack of transparency in their operations. Therefore, in an increasingly challenging external environment, with an ever-demanding community, the need to know how mosques are managed and how they serve as community centers to maintain high standards of Muslim activities is as great as ever; hence the need for this paper.